Role of Eucalypts in Agroforestry and Essential Oil Production Potential - Shiva, M. P.; Prakash, Om; Singh, Surendra; Jaffer, Rubab (Indian Forester, 1988)
Eucalyptus controversy has been raging for the last couple of years that its plantations have been causing damage to water-table and soil. But data collected from Central Tarai Forest Division, Haldwani, G.B. Pant University of Agriculture and Technology, Pantnagar (Nainital) and other source, reveal that growth and yield of the plants of Gramineae family including paddy and aromatic grasses is improved with the Eucalyptus leaf litter. No adverse effect of Eucalyptus on the agricultural crops and aromatic grasses has been noticed. Production potential and economics of land use increases if Eucalyptus is judiciously planted.